Responsibility, Respectability, Recognition, and Polyamory: Lessons in Subject Formation in the Age of Sexual Identity - Obadia, Julienne (Feminist studies, 2020)
The discursive shift that polyamory exemplifies, from the free love movement of the 1960s, with its countercultural critiques of social repression, to the expansion of identity-based formulations of immutable sexuality, was made possible in part by the gay rights movement and its legal victories against discrimination grounded in the growing legitimacy of the "born-this-way" subject. As in the nineteenth century, this subject's desires are understood to reside entirely in a pre-discursive interior where they reveal core truths about oneself. However, that subject has now been formally recognized as worthy of dignity and protection, and their treatment even serves as a gauge of progress in mainstream debates. This configuration has taken shape amid the broad entrenchment of neoliberal forms of personhood wherein people are increasingly required to make choices based on interior scrutiny and self-discovery across domains including employment and health. It is further buttressed by the dramatic narrowing of available discourses about desire into two mutually exclusive options, variously cast as nature/nurture, biology/ choice, and orientation/lifestyle. In this framework, claims for recognition can be made based on characteristics deemed innate but not those understood as choices. My argument thus proceeds from the observation that the classic liberal "march of progress" has, in recent decades, formed a queue that shapes the recognizability of marginal identities and practices as valid and worthwhile according to the contours of what came before.